Interactive means of motivating students to learn English for specific purposes at agrarian and technical universities (Educational Dimension, 2020)
The article presents the analysis of the implementation of interactive technologies at the English for specific purposes lessons for motivating students at agrarian and technical universities. It is emphasized that the use of an interactive learning model, which includes modelling life situations, the use of role-playing games, joint problem solving, effects students’ motivation. Unlike the subject-object approach, the students become the subjects of interaction; they actively participate in the learning process, following their individual route. The students acquire knowledge in the process of interactive learning not in the finished form, but obtain it themselves, in the process of their own activity. Therefore, the goal of the teacher is to create the conditions under which the students will discover new knowledge, construct it, and use it. It is noted that the process of learning a foreign language for special purposes requires the creation of a mixed learning environment, in which a new type of cooperation between teachers and students emerges. The authors gave the examples of the use of interactive learning technology which can improve the training of future professionals and ensure the formation of the professional foreign language communication skills. The results of experimental implementation of interactive means for developing students’ motivation are presented.
Keywords: interactive learning technology; interactive teaching methods; English for specific purposes (ESP); communicative competence; agrarian university; technical university